Traditional Chinese Medicines as Effective Reversals of Epithelial-Mesenchymal Transition Induced-Metastasis of Colorectal Cancer: Molecular Targets and Mechanisms - Ge, Hongzhang; Xu, Chao; Chen, Haitao; Liu, Ling; Zhang, Lei; Wu, Changhong; Lu, Yi; Yao, Qinghua (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is the third most common type of cancer worldwide. Distant metastasis is the major cause of cancer-related mortality in patients with CRC. Epithelial-mesenchymal transition (EMT) is a critical process triggered during tumor metastasis, which is also the main impetus and the essential access within this duration. Therefore, targeting EMT-related molecular pathways has been considered a novel strategy to explore effective therapeutic agents against metastatic CRC. Traditional Chinese medicines (TCMs) with special properties multi-target and multi-link that exert their therapeutic efficacies holistically, which could inhibit the invasion and metastasis abilities of CRC cells via inhibiting the EMT process by down-regulating transforming growth factor-β (TGF-β)/Smads, PI3K/Akt, NF-κB, Wnt/β-catenin, and Notch signaling pathways. The objective of this review is to summarize and assess the anti-metastatic effect of TCMs by mediating EMT-associated signaling pathways in CRC therapy, providing a foundation for further research on the exact mechanisms of action through which TCMs affect EMT transform in CRC.